Saṁvidullāsaḥ = Saṃvidullāsaḥ : manifestation of divine consciousness : Swami Lakshman Joo, saint-scholar of Kashmir Śaivism, a centenary tribute - Lakshman Joo; Bäumer, Bettina; Sarla Kumar (D.K. Printworld, 2007)
Contributed articles chiefly on the life and works of Swami Lakshman Joo, 1907-1991, scholar of Kashmir Śaivism; includes Sanskrit passages with translation.